Chronic Kidney Disease and Infection Risk: A Lower Incidence of Peritonsillar Abscesses in Specific CKD Subgroups in a 16-Year Korean Nationwide Cohort Study - Mi Jung Kwon; Ho Suk Kang; Joo-Hee Kim; Ji Hee Kim; Woo Jin Bang; Dae Myoung Yoo; Na-Eun Lee; Kyeong Min Han; Nan Young Kim; Hyo Geun Choi; Min-Jeong Kim; Eun Soo Kim (Microorganisms)
Peritonsillar abscesses and deep neck infection are potentially serious infections among patients with chronic kidney disease (CKD), posing risks for severe complications and drawing significant public health concern. This nationwide, population-based longitudinal study (2002–2019) assessed the extended relationship between chronic kidney disease (CKD) and the likelihood of peritonsillar abscess and deep neck infection in a Korean cohort. Using a 1:4 propensity score overlap-weighted matching, we included 16,879 individuals with CKD and 67,516 comparable controls, accounting for demographic variables and comorbidities to ensure balanced group comparisons. Hazard ratios (HRs) and 95% confidence intervals (CIs) for deep neck infection and peritonsillar abscesses in relation to CKD history were calculated with a propensity score overlap-weighted Cox proportional hazards model. Our results revealed no significant increase in the overall incidence of deep neck infections or peritonsillar abscesses in CKD patients compared to controls. Interestingly, CKD patients demonstrated a 50% reduced likelihood of developing peritonsillar abscesses (HR 0.50; 95% CI = 0.30–0.83; p = 0.007), particularly among subgroups aged 70 years or older, females, non-smokers, rural residents, overweight individuals, and those with lower comorbidity burdens (e.g., absence of hypertension, hyperlipidemia, or hyperglycemia). In summary, the results suggest that lifestyle modifications and the effective management of comorbidities could reduce the risk of peritonsillar abscess in certain CKD subgroups. Our findings may help to alleviate public health concerns regarding peritonsillar abscesses and deep neck infections as CKD-related comorbidities.